Characterizing avocado production systems for Ugandan exports: the need for consolidation and support for sustainable development - Sseruwagi, Peter; Lehmann, Edouard; Sigombe, Paul; Ddamulira, Gabriel; Van Casteren, Jan Willem; De Bauw, Pieterjan (Frontiers in Sustainable Food Systems, 2025)
Hass avocado production and trade are rapidly expanding globally, with increasing consumer demands on quality, safety and sustainability. Last decade, the contribution of East Africa has increased tremendously following several comparative advantages. However, despite substantial recent public and private investments, Uganda’s Hass production and export lags behind neighboring countries. This is mainly due to the sector’s limited organization, resulting in a fragmented market with varying socio-economic, environmental, and agronomic conditions. Consequently, the limited data and insights on these variable production systems negatively impact the effectiveness of interventions and investments in the sector. In this study, Hass avocado producers were randomly selected across Uganda. Field visits included farm and field surveys, GPS mapping of production areas, and soil sampling for wet-chemistry analysis. Descriptive statistics, multivariate logistic regression, and ANOVA were used to assess the impact of farm and field characteristics on production practices and access to advisory services and certification. Farming systems and dynamics were characterized by assessing demographics, economic data, marketing, farmer organization, and farming practices including soil and nutrient management, irrigation, pest and disease control, and post-harvest management. Results show a fragmented and immature but expanding Hass sector in Uganda. Production mostly occurs in small- to medium-sized fields with no or limited inputs (i.e., fertilisers, pesticides, irrigation), using manual labor (family or hired) under mixed cropping systems, but lacking critical infrastructure, agronomic knowledge, extension services, and access to markets. In contrast to farmer’s belief that soils are suitable and fertile for Hass avocado, soil analyses indicate the urgent need for site specific soil management interventions. Implementation of good agronomic practices and access to inputs and advisory services seem mostly related to farm and field size, and to a lesser extent influenced by farmer age, orchard age, and agroecology, while membership of farmer organizations/associations currently seem to bring limited benefits. This study highlights several comparative advantages and opportunities for the Hass sector in Uganda and identifies the priority challenges to be tackled in future investments and interventions targeting a sustainable avocado industry.